3213 Unraveling the role of Phospholamban (PLN) in humans via the characterization of Induced Pluripotent Stem Cell (iPSC) Cardiomyocytes (CM) derived from carriers of a lethal PLN mutation. (27th March 2019) - Trivieri, Maria Giovanna; Stillitano, Francesca; Ceholski, Delaine; Turnbull, Irene; Costa, Kevin; Weber, Thomas; Fish, Kenneth; Kranias, Evangelia; Hajjar, Roger
Abstract : OBJECTIVES/SPECIFIC AIMS: To study the biology of Phosholamban (PLN) in a human relevant model. METHODS/STUDY POPULATION: State of the art stem-cell technologies using iPSC-CMs derived from carriers of a lethal PLN mutation. RESULTS/ANTICIPATED RESULTS: Our preliminary data demonstrate that this particular PLN mutation (L39) results in reduced expression and mis-localization of PLN as well as increased incidence of early after depolarization in isolated iPSC-CMs. DISCUSSION/SIGNIFICANCE OF IMPACT: Phospholamban (PLN) is a critical regulator of Ca++ homeostasis yet many uncertainties still remain regarding its role in humans. Our study will provide unique insights into the pathophysiology of this protein in HF.